Cover Image. Issue 1 (21st January 2021) - Swanson, Frederick J.; Gregory, Stanley V.; Iroumé, Andres; Ruiz‐Villanueva, Virginia; Wohl, Ellen
Abstract : The cover image is based on the Original Article Reflections on the History of Research on Large Wood in Rivers by Frederick J. Swanson et al., https://doi.org/10.1002/esp.4814 . The cover image depicts Large wood in Lookout Creek, H.J. Andrews Experimental Forest, western Cascade mountains, Oregon, USA, which is the location of studies of effects of large wood on river geomorphology and ecology. The image was created using a "painting‐with‐light" technique by David Paul Bayles and is part of his Outside of Time ‐ Forest Landscapes collection published in Terrain.org, where he explains his motivations and methods. Used with permission of the photographer.